2020
DOI: 10.1507/endocrj.ej20-0201
|View full text |Cite
|
Sign up to set email alerts
|

Fasting serum total bile acid levels are associated with insulin sensitivity, islet <i>β</i>-cell function and glucagon levels in response to glucose challenge in patients with type 2 diabetes

Abstract: Type 2 diabetes (T2D) is characterized by islet β-cell dysfunction and impaired suppression of glucagon secretion of α-cells in response to oral hyperglycaemia. Bile acid (BA) metabolism plays a dominant role in maintaining glucose homeostasis. So we evaluated the association of fasting serum total bile acids (S-TBAs) with insulin sensitivity, islet β-cell function and glucagon levels in T2D. Total 2,952 T2D patients with fasting S-TBAs in the normal range were recruited and received oral glucose tolerance tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The effects of exogenous insulin were eliminated by calculating β-cell secretion and insulin resistance indices based on C-peptide levels. The trapezoidal principle for reflection β-cell secretion was used to calculate the C-peptide area under the curve (AUCCP) ( 18 ), and insulin resistance was measured based on the HOMA-IRCP, which was calculated as (fasting glucose × fasting C-peptide)/22.5 ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of exogenous insulin were eliminated by calculating β-cell secretion and insulin resistance indices based on C-peptide levels. The trapezoidal principle for reflection β-cell secretion was used to calculate the C-peptide area under the curve (AUCCP) ( 18 ), and insulin resistance was measured based on the HOMA-IRCP, which was calculated as (fasting glucose × fasting C-peptide)/22.5 ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Increased fasting serum BAs were associated with IR, impaired islet BC function, and increased glucagon levels in patients with T2D. 34 Cariou et al 15 reported 1.6-fold increases in DCA in patients with T2D and insulin resistance index (HOMA-IR) was positively related with CA, CDCA, and DCA after adjustment for potential confounders. In addition, Hou et al 19 showed that serum total BA level was positively correlated with HOMA-IR and pancreatic BC insulin secretion (HOMA-beta) and increased risk of GDM in Chinese women.…”
Section: Discussionmentioning
confidence: 94%
“…Serum C-peptide (CP) levels were measured by the chemiluminescence method in an immunoassay system (DxI 800, Beckman Coulter) with the inter-assay and intra-assay CVs < 4.0%. In order to eliminate the influence of exogenous insulin, HOMA-IR CP which was defined as (fasting glucose × fasting CP)/22.5 was adopted as an indicator of insulin resistance ( 17 ). Serum OC, CTx, PINP, parathyroid hormone (PTH) and vitamin D levels were analyzed on an automated immunoassay system (iSYS, Immunodiagnostic Systems Ltd., Boldon) using a chemiluminescence method.…”
Section: Methodsmentioning
confidence: 99%